The genus Habenaria (Orchidaceae) in Thailand - Kurzweil, Hubert (Thai Forest Bulletin (Botany), 2014)
The taxonomy of the Thai species of the largely terrestrial orchid genus Habenaria Willd. is reviewed. Forty-six species are recognised. H. humidicola Rolfe, H. poilanei Gagnep. and H. ciliolaris Kraenzl. are newly recorded for Thailand based on a single collection each, although the identifi cation of the latter two is uncertain. An aberrant specimen of H. viridifl ora (Rottler ex Sw.) Lindl. is pointed out. H. erichmichaelii Christenson is reduced to synonymy under H. rhodocheila Hance. Several diffi cult and geographically widespread species complexes are identifi ed and the need for future studies of all of the available material over the entire distribution range is emphasized. Based on the herbarium and spirit material examined here the following distribution pattern emerged: about 53 % of all collections of Thai Habenaria species were made in northern Thailand (although this may partly be due to collector’s bias) and about 15 % in north-eastern Thailand, while only between 4.5 and 7.5 % come from each of the other fl oristic regions of the country. In addition, an assessment of the conservation status has been made in all species. The present study will form the basis for a later contribution to the Flora of Thailand.